Outcomes of Haploidentical Transplantation in Patients with Relapsed Multiple Myeloma: An EBMT/CIBMTR Report - Sahebi, Firoozeh; Garderet, Laurent; Kanate, Abraham S.; Eikema, Diderik Jan; Knelange, Nina Simone; Alvelo, Omar F.Dávila; Koc, Yener; Blaise, Didier; Bashir, Qaiser; Moraleda, José M.; Dreger, Peter; Sanchez, James F.; et al. (Biology of Blood and Marrow Transplantation, 2018)
Allogeneic hematopoietic cell transplantation (allo-HCT) using siblings and matched donors has the potential for long-term disease control in a subset of high-risk patients with multiple myeloma (MM); however, the data on using haploidentical donors in this disease are limited. We conducted a retrospective analysis to examine the outcomes of patients with MM who underwent haploidentical allo-HCT within European Society for Blood and Marrow Transplantation/Center for International Blood and Marrow Transplant Research centers. A total of 96 patients underwent haploidentical allo-HCT between 2008 and 2016. With a median follow-up of 24.0 months (range, 13.2 to 24.9 months), 97% (95% confidence interval [CI], 93% to 100%) of patients had neutrophil engraftment by day 28, and 75% (95% CI, 66% to 84%) achieved platelet recovery by day 60. Two-year progression-free survival (PFS) was 17% (95% CI, 8% to 26%), and overall survival (OS) was 48% (95% CI, 36% to 59%). At 2 years, the cumulative risk of relapse/progression was 56% (95% CI, 45% to 67%), and 1-year nonrelapse mortality (NRM) was 21% (95% CI, 13% to 29%). The incidences of acute graft-versus-host-disease (GVHD) grades II-IV by 100 days and chronic GVHD at 2 years were 39% (95% CI, 28% to 49%) and 46% (95% CI, 34% to 59%), respectively. On univariate analysis, use of post-transplantation cyclophosphamide (PT-Cy) (54% [95% CI, 41% to 68%] versus 25% [95% CI, 1% to 48%]; P =.009) and use of bone marrow as source of stem cells (72% [95% CI, 55% to 89%] versus 31% [95% CI, 17% to 46%]; P = .001) were associated with improved OS at 2 years. Disease status, patient sex, intensity of conditioning regimen, recipient/donor sex mismatch, and cytomegalovirus serostatus had no impact on OS, PFS, or NRM. Haploidentical transplantation is feasible for patients with multiply relapsed or high-risk MM, with an encouraging 2-year OS of 48% and an NRM of 21% at 1 year, supporting further investigation of haploidentical allo-HCT in suitable candidates with MM.
EVALuna2:35108